Cheap talks with uncertainty in expert’s preferences - Calderón Sánchez, Juan Eduardo (Estudios Económicos de El Colegio de México, 2009)
This paper models the strategic information transmission employed by Crawford-Sobel introducing a variant to the lead example of Dimitrakas-Sarafidis. The expert type space has two dimensions; the expert has the private information over two parameters, the state and his bias. The space of actions of the decision maker has only one dimension. We suppose that the state lies in the interval [0,1], but the expert bias lies in the interval [-1,1]. We find that the equilibriums are also in partitions, but there is not equilibrium for all positive integer, the most informative equilibrium exists for a partition of size 3.